5-Hydroxymethylcytosine Signatures in Circulating Cell-Free DNA as Early Warning Biomarkers for COVID-19 Progression and Myocardial Injury - Chen, Hang-yu; Li, Xiao-xiao; Li, Chao; Zhu, Hai-chuan; Hou, Hong-yan; Zhang, Bo; Cheng, Li-ming; Hu, Hui; Lu, Zhong-xin; Liu, Jia-xing; Yang, Ze-ruo; Zhang, Lei; et al. (Frontiers in Cell and Developmental Biology, 2022)
Background The symptoms of Coronavirus Disease 2019 (COVID-19) range from moderate to critical conditions leading to death in some patients, the early warning indicators of the COVID-19 progression and the occurrence of its serious complications such as myocardial injury are limited. Methods We carried out a multi-center, prospective cohort study in three hospitals in Wuhan. Genome-wide 5hmC profiles in plasma cell-free DNA (cfDNA) was used to identify risk factors for COVID-19 pneumonia and developed a machine learning model using samples from 53 healthy volunteers, 66 patients with moderate COVID-19, 99 with severe COVID-19, and 38 with critical COVID-19. Results Our warning model demonstrated an area under the curve (AUC) for 5hmC warning moderate patients developed into severe status was 0.81 (95%CI 0.77-0.85), and severe patients developed into critical status was 0.92 (95% CI 0.89-0.96). We further built a warning model on patients with and without myocardial injury with the AUC of 0.89 (95%CI 0.84-0.95). Conclusion This is the first study showing the utility of 5hmC as an accurate early warning marker for disease progression and myocardial injury in COVID-19 patients. Our results show that PDE4D and TET2 may be important markers in the progression of COVID-19 disease.